ҚЫТАЙ ТІЛІНДЕГІ ТҰРАҚТЫ СӨЗ ТІРКЕСТЕРДІ АУДАРУ ЖОЛДАРЫ. - Қалиқан, Ә. (Journal of Oriental Studies, 2016)
Бұл мақалады қазақ тіліне аудару жолдарын айқын-дайтын зерттеу жұмысы арқылы екі халықтың сөздікқұрамының ерекшеліктерімен танысып, сонымен қатар,қытай тілін үйренушілер үшін тіл байлығын кеңейтуге,қытай мәдениетін терең түсінуге мүмкіндік береді.Idioms is the crystallization of language development.Thinking it new, refined form, people with a strong sense ofbeauty. Primarily reflected in its brief to the expression ofsemantics. At the same time, it is often the sentence and theuse of special materials and various figures of speech, Afeast for the eyes produce their form of the language. Paperon the cultural differences between English and Chineseidioms of its three main translation, transliteration,translation, live translation.